Miniaturizace a zvýšení dosahu modulu W-DMX v1.0 - Rojček, Martin (Vysoké učení technické v Brně. Fakulta informačních technologií, 2015)
Cílem diplomové práce bylo navrhnout bezdrátový systém, který by byl primárně určen pro použití v oblasti světelné techniky. Umožnil by bezdrátové propojení světelných zařízení komunikujících protokolem DMX512 prostřednictvím bezdrátového transceivera nRF2401A. Vychází z návrhu, který však nebyl kvůli svým poměrně velkým rozměrům a krátkému dosahu prakticky použitelný. Nedostatek krátkého dosahu práce řeší RF zesilovačem RF5722, přičemž se zabývá i jeho dalšími možnostmi jako použitím antén s větším ziskem, obvody typu Front-end a frekvenčním agilním protokolem založeným na přeskakování frekvence. Práce se současně soustředí na minimalizaci rozměrů modulu použitím SMD součástek a netriviálních konstrukčních úprav a to se snahou umístit jej do konektoru XLR. DPS systému je navržena v prostředí Eagle.

The aim of this master thesis is to design a wireless system which would be primarily used for a control of stage lighting. Our idea is to establish wireless links, that will carry DMX512 protocol, between individual lighting devices based on wireless transceiver nRF2401A. The foundation of our project comes from a previous design, which was not completely suitable for a practical use because of its rather large proportions and a short RF range. The project resolves the issue of relatively short range coverage through the deployment of RF amplifier RF5722. In the same tme, it also takes into account other technical aspects such as the use of antenas with a higher gain, front-end circuits or increased transmission reliability through frequency hopping scheme. Proper attention is also given to a minimalization of the module dimensions by using SMD components and layout adjustements, so it would be possible to place the whole board inside XLR connector. Set of printed circuit boards with the specified characteristics, which is the expected outcome of our project, were designed with Eagle PCB design environment.
Miniaturization and Range Extension of W-DMX v1.0 Module
Keywords: Miniaturizace; vestavěný systém; bezdrátový přenos; transceiver; zvýšení dosahu; HCS08; RF zesilovač; DMX512; XLR; Front-end.; Miniturization; Embedded System; Wireless Communication; Transceiver; Range Extension; HCS08; DMX512; RF amplifier; XLR; Front-end.